Sedekah QR (SQR): Charity System in Modern Era - Muhammad Al Faridho Awwal (Jurnal Ilmiah Ekonomi Islam, 2021)
Badan Amil Zakat Nasional (Baznas) has launched a donation system with QR code on Friday, December 22th 2017. Baznas’ Deputy Chief, Arifin Purwakananta said the usage of QR code was the first in alms services. Other than using QR code, Baznas also cooperated with various online multipayment services such as Go-Pay and OVO. Observing such trends, by using research with qualitative and quantitative approach and modifying both Theory of Planned Behavior and Technology Acceptance Models, this research aims to formulate the concept of cashless alms donation payment done by every feasible mosque and to discover society’s interest toward alms donation using QR code. Therefore, there need to be a synergy between Otoritas Jasa Keuangan (OJK) as financial transaction supervisor and Dewan Masjid Indonesia (DMI) as the highest position in mosques’ management in Indonesia. This direct collection approach done by this service is expected to increase mosques’ welfare and the communities around mosques so that the equality of welfare to all mosques can happen